Conservative management and postoperative return to sport in endurance athletes with flow limitations in the iliac arteries: a scoping review - Arnold, J. I.; Mawji, A.; Stene, K.; Taylor, D. C.; Koehle, M. S. (Sports Medicine, 2024)
Background: Flow limitations in the iliac arteries (FLIA) is a sport-related vascular condition increasingly recognised as an occupational risk for professional cyclists and other endurance athletes. Surgical reconstruction is the definitive treatment for athletes wishing to continue competition. However, less information has been published regarding conservative management options and return-to-sport (RTS) guidelines. Objective: Our aim was to review the existing literature on conservative treatment of FLIA, identify knowledge gaps and propose an RTS framework for athletes returning to competition. Methods: A comprehensive literature review was performed using the Ovid-MEDLINE, PubMed, Embase and PEDro databases for publications relevant to conservative management of FLIA. A scoping review was conducted following PRISMA-ScR guidelines. Original, peer-reviewed publications in English describing conservative or postoperative management for athletes with FLIA were included. Additional grey literature and clinical expertise were consulted to inform RTS guidelines. Results: Overall, 62 studies were included in this review. In total, 11 categories of conservative modalities were extracted and presented qualitatively in terms of the information source (discussion or results statements) and perspective of the authors (positive, negative or mixed). We have proposed RTS guidelines covering pre-operative preparation and postoperative rehabilitation based on the available literature, clinical experience, and drawing from other areas of sports medicine research. Conclusion: There is insufficient literature evaluating the effectiveness of conservative management options for FLIA to establish best practices. Considering the importance of RTS for competitive athletes, we proposed practical guidelines to help with clinician and patient decision making. Future consensus should be sought for RTS best practices.